1986
DOI: 10.1002/macp.1986.021870620
|View full text |Cite
|
Sign up to set email alerts
|

Conformational analysis of higher poly(oxyalkylenes) using empirical force field calculations

Abstract: The conformational energies for the various rotational isomers of model compounds for poly(oxytrimethylene), POM, , and poly(oxytetramethylene), P O W , were calculated by means of the empirical force field method, and statistical mechanics calculations were made for the configuration-dependent properties of POM3 and PO&. Although the dipole moment ratios of these polymers directly calculated from the results of the force field calculations agreed well with the observed ones, the estimated characteristic ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

1988
1988
1996
1996

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 7 publications
1
7
0
Order By: Relevance
“…Besides the present study, only Miyasaka et al have reported explicit values for E χ ‘ ‘ , E χ ‘ , and E κ (see footnote f in Table ) for POM 3 . In close agreement, both studies find that E χ ‘ ‘ is small and positive while E χ ‘ is small and negative.…”
Section: Resultsmentioning
confidence: 53%
See 4 more Smart Citations
“…Besides the present study, only Miyasaka et al have reported explicit values for E χ ‘ ‘ , E χ ‘ , and E κ (see footnote f in Table ) for POM 3 . In close agreement, both studies find that E χ ‘ ‘ is small and positive while E χ ‘ is small and negative.…”
Section: Resultsmentioning
confidence: 53%
“…The energies listed in Table were all obtained from molecular mechanics calculations; hence it can be assumed that the E σ values do not reflect the extra stabilization of gauche states derived from the oxygen gauche effect. At the same time, the value E σ = −0.4 kcal mol -1 from Miyasaka et al . appears to factor in some portion of this observed effect.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations